Examining the Impact of Electronic Game Usage on Kindergarten Children's Behavior in the Sharazur District: Insights from Parental Perspectives - Salih, Fryad Majeed; Salih, Mihraban Hussein; Darwesh, Farah Taha; Abdulla, Mawdud Jabar (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research investigates the detrimental effects of electronic game use on the behavior of kindergarten children, with a focus on gender disparities, as perceived by parents in the Sharazoor district. The study, employing descriptive methods, encompasses a sample of 160 equally distributed children of both genders from kindergartens affiliated with the Directorate of Education of Sharazoor—specifically, Mastan, Chro, Sara, and Papula. Utilizing a survey form comprising 32 items, the researchers statistically analyze the collected data, assigning three response options (Yes, Sometimes, No) with corresponding marks (3,2,1).The psychometric measures, including arithmetic mean, discriminant values, T values for one and two samples, Jetman statistical coefficient for distribution, and Cooper statistical coefficient using the t.test, were employed for data analysis. The key findings reveal that 90% of boys (72 out of 80) engage in electronic game usage, while 75% of girls (60 out of 80) participate in such activities. This discrepancy underscores a notable difference in electronic game usage between boys and girls in the experimental community, indicating a higher prevalence of electronic game addiction among boys. The study concludes with several recommendations for mitigating the negative impact of electronic game use on kindergarten children's behavior, acknowledging the importance of gender-sensitive interventions in addressing this issue.